2014
DOI: 10.1021/sc5001622
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Carbon Footprint of Linear Alkylbenzenesulfonate from Coconut Oil, Palm Kernel Oil, and Petroleum-Based Paraffins

Abstract: Beyond renewable liquid transportation fuels from biomass feedstocks, there is great interest to use renewable feedstocks for sustainable chemical production. The goal of this study is to conduct an original cradle-to-grave carbon footprint for linear alkylbenzenesulfonate (LAS) using petroleum, coconut oil, and palm kernel oil derived paraffins, and including end of life emissions during wastewater treatment. The fully petroleum pathway to LAS was modeled using new inputs from industry (UOP). Mass allocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…The injection temperature was at 300 °C. 3 [TFSI]/AlCl3 ionic liquids showed biphasic behavior. Typically, a certain amount of AlCl3 can be homogeneously dissolved in this kind of ionic liquids up to the lower limit of biphasic regime.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…The injection temperature was at 300 °C. 3 [TFSI]/AlCl3 ionic liquids showed biphasic behavior. Typically, a certain amount of AlCl3 can be homogeneously dissolved in this kind of ionic liquids up to the lower limit of biphasic regime.…”
Section: 3mentioning
confidence: 99%
“…Synthetic detergents made from branched alkyl benzene (BAB) have been widely applied in all sorts of areas in our daily life. [1][2][3][4] However, the increasing usage of detergent leads to branched alkyl benzene sulfonate (BAS) accumulation and environmental contamination. Generally, it is known that synthetic detergent made from linear alkyl benzene (LAB) has better biodegradability than that made from BAB or natural soap.…”
Section: Introductionmentioning
confidence: 99%
“…Until today the number of LCA studies performed for the production of surfactants has been limited, while LCA assessments are mainly focused on their application as detergents and cleaning products. [36][37][38][39][40] Although there is still not a widely accepted definition for 'green surfactants', or else 'biosurfactants', for practical reasons, most of the time, biosurfactants are described as substances of biological origin. 41 For example, in their study Guilbot et al 37 explored the case of an alkyl polyglucoside (APG), composed of cetearyl glucoside and cetearyl alcohol derived from palm kernel oil.…”
Section: Overview Of Results Of the Fermentation Processes For Sophormentioning
confidence: 99%
“…Medusa was adopted to evaluate the concentration of Zn or Si species from hemimorphite as a function of pH; the plot is presented in Figure 10. It demonstrated that in acidic solutions, Zn 2+ ions dominate in water, and under pH > 11.5, Zn species mainly exists as Zn(OH) 2 Under pH 7.0-11.0, HDDPA mainly exists as HDDPA 3− species in aqueous solutions, Zn(OH)2 and ZnSiO3 might be the main Zn species on hemimorphite surfaces, and some ZnOH + species would be adsorbed on to hemimorphite surfaces. Therefore, HDDPA 3− might react with Zn(II) species of hemimorphite surfaces to form Zn(II)-HDDPA surface complexes.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are prerequisites to froth flotation, which is the most principal process for enrichment and separation of value minerals from their ores [1][2][3][4][5]. In froth flotation, a collector (one kind of surfactant) selectively attaches to a target mineral using its minerophilic group, and then its hydrophobic group attaches to air/nitrogen bubbles which delivers the mineral particles to the slurry interface [6,7].…”
Section: Introductionmentioning
confidence: 99%